2022
DOI: 10.3389/fpls.2022.843565
|View full text |Cite
|
Sign up to set email alerts
|

The Regulation of Pea (Pisum sativum L.) Symbiotic Nodule Infection and Defense Responses by Glutathione, Homoglutathione, and Their Ratio

Abstract: In this study, the roles of glutathione (GSH), homoglutathione (hGSH), and their ratio in symbiotic nodule development and functioning, as well as in defense responses accompanying ineffective nodulation in pea (Pisum sativum) were investigated. The expression of genes involved in (h)GSH biosynthesis, thiol content, and localization of the reduced form of GSH were analyzed in nodules of wild-type pea plants and mutants sym33-3 (weak allele, “locked” infection threads, occasional bacterial release, and defense … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 72 publications
0
7
0
Order By: Relevance
“…The upregulation of genes encoding the GSH biosynthesis enzymes (PsGSH1, PsGSHS) in heat-stressed nodules observed in this study may also indicate the link to oxidative stress. Indeed, in early senescent nodules of the mutant sym40-1, the genes of glutathione biosynthesis were upregulated, while the content of GSH was low compared to the wild type [37].…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…The upregulation of genes encoding the GSH biosynthesis enzymes (PsGSH1, PsGSHS) in heat-stressed nodules observed in this study may also indicate the link to oxidative stress. Indeed, in early senescent nodules of the mutant sym40-1, the genes of glutathione biosynthesis were upregulated, while the content of GSH was low compared to the wild type [37].…”
Section: Discussionmentioning
confidence: 97%
“…viciae 3841 strain on the pea line SGE was investigated. This symbiotic pair is actively used as a model system for various studies of nodule development in peas [32,[37][38][39][40]. Heat-stressed nodules changed their color from pink to green at their In nodules exposed to 21 • C for 12 days, a green color was seen at the base of the nodule, which indicated the formation of the senescence zone (Figure 7G,H).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, the important factor of the senescence onset is the age-related shift in the nodule redox status. Thus, Ivanova and co-workers showed that a functional metabolically active nodule requires high amounts of reduced glutathione (GSH) in tissues, whereas accumulation of its oxidized form (GSSG) correlated with nodule senescence [192]. Fukudome et al also found that the nodule content of nitric oxide (NO) is one of the key regulators of nodule senescence.…”
Section: Nodule Senescencementioning
confidence: 99%